Identifying marine phytoplankton (Academic Press, 1997)
dentifying Marine Phytoplankton is an accurate and authoritative guide to the identification of marine diatoms and dinoflagellates, meant to be used with tools as simple as a light microscope. The book compiles the latest taxonomic names, an extensive bibliography (referencing historical as well as up-to-date literature), synthesis and criteria in one indispensable source. Techniques for preparing samples and containing are included as well as hundreds of detailed, helpful information.